The Neutrophil-to-Lymphocyte Ratio as a Biomarker in Metastatic Castrate-Sensitive Prostate Cancer Patients Treated with Abiraterone Acetate - Caio Vinícius Suartz; Marie-Laurence Roy; Paul Toren (Société Internationale d’Urologie Journal)
Given its known prognostic role, we aimed to investigate the role of neutrophil–lymphocyte ratio (NLR) as a biomarker in metastatic castration-resistant prostate cancer (mCRPC) patients receiving ADT, either as monotherapy or in conjunction with abiraterone acetate (AA) and prednisone. This retrospective cohort study analyzed the LATITUDE study of men with high-risk mCSPC. Patients were assigned to receive either AA, prednisone, and androgen deprivation therapy (ADT) or placebo plus ADT. Using a previously established NLR threshold of 2.5, we evaluated if this could predict clinical response to abiraterone. At baseline, there were no significant differences in NLR values between the treatment groups. Of the known baseline prognostic factors, NLR was associated with albumin levels and Eastern Cooperative Oncology Group performance scores. Moreover, the number of bone metastases was higher in patients with NLR ≥ 2.5. On multivariable analysis, baseline NLR ≥ 2.5 did not predict overall survival, PSA progression-free, or metastasis-free survival. However, changes in PSA and NLR at six months indicated distinct survival patterns between the placebo and AA groups, suggesting the potential for their combined assessment as a prognostic tool. Baseline NLR was not an independent predictor factor for response to AA in the LATITUDE study, though NLR changes at 6 months may predict better survival beyond PSA values alone. Further research is required to better understand in which patients with advanced prostate cancer NLR changes may be a useful prognostic tool.